2011
DOI: 10.1073/pnas.1105115108
|View full text |Cite
|
Sign up to set email alerts
|

The Ca V 3.3 calcium channel is the major sleep spindle pacemaker in thalamus

Abstract: Low-threshold (T-type) Ca2+ channels encoded by the Ca V 3 genes endow neurons with oscillatory properties that underlie slow waves characteristic of the non-rapid eye movement (NREM) sleep EEG. Three Ca V 3 channel subtypes are expressed in the thalamocortical (TC) system, but their respective roles for the sleep EEG are unclear. Ca V 3.3 protein is expressed abundantly in the nucleus reticularis thalami (nRt), an essential oscillatory burst generator. We report the characterization of a transgenic Ca V 3.3 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
222
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(248 citation statements)
references
References 30 publications
25
222
1
Order By: Relevance
“…1F). These results are consistent with those reported previously (22) and suggest that Ca V 3.3 is responsible for most T-type Ca 2+ currents in TRN neurons. The small amount of residual current observed in Ca V 3.3 −/− neurons at -40 mV is probably mediated by Ca V 3.2 and as observed previously (22).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1F). These results are consistent with those reported previously (22) and suggest that Ca V 3.3 is responsible for most T-type Ca 2+ currents in TRN neurons. The small amount of residual current observed in Ca V 3.3 −/− neurons at -40 mV is probably mediated by Ca V 3.2 and as observed previously (22).…”
Section: Resultssupporting
confidence: 93%
“…The mAHPs prevent an excessive increase in axon fiber excitability and contribute to the gradual decrease in tonic firing rate during a continuous activity. In TRN neurons, the mAHP is largely dependent on Ca V 3.3 T-type channels that are the major T-type Ca 2+ channel in this region (22). In Ca V 3.3 −/− and Ca V 3.2 −/− /3.3 −/− mice, the mAHP is greatly reduced due to the lack of T-type channels.…”
Section: Methodsmentioning
confidence: 99%
“…Statistics are described in the text. (Astori et al 2011;Halassa et al 2011). The RTN is characterized by a rather homogenous population of GABAergic neurons, expressing high levels of the "slow Ca 2ϩ buffer" PV (Celio 1990;Schwaller 2009 (Talley et al 1999) are associated with the bursts of discharges that characterize most RTN cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis of a PV-EGFP reporter mouse line (Meyer et al 2002) showed that in the RTN a minority (6% Ϯ1) of the neurons were PV negative (data not shown). It has been recently proposed that the tonically firing cells are characterized by a lower responsiveness to low Ca 2ϩ currents, I T (Lee et al 2007), possibly due to a large difference in the distal vs. proximal distribution of the LVA channels Ca v 3.2 and Ca v 3.3, (Crandall et al 2010), or due to the lack of Ca v 3.3, which is essential for LTS (Astori et al 2011). On the whole it appears that this cell population has physiological properties that are distinct from the bursting types and are independent of the presence of PV.…”
Section: Four Firing Types Characterize the Mouse Rtnmentioning
confidence: 99%
“…Cav3.3 T-type calcium channels are mainly expressed in the cerebrum, spinal cord, dorsal root ganglion (DRG) neurons, adrenal cortex and thyroid gland. It has been shown that Cav3.3 in nucleus reticularis thalami is involved with the sleep spindles, a hallmark of natural sleep [12]. To date, there is no specific blocking agent for T-type calcium channels.…”
Section: Introductionmentioning
confidence: 99%